Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa SMPN 1 Cikancung Melalui Pendekatan Kontekstual - Mayang Sinta Frestianti; Gagan Aditya Fauzan; M. Diki Fadilah; Risma Amelia (Departement of Mathematics Education, 2020)
This research was conducted at Cikancung 01 Middle School on class VIII triangle material. This research uses the